Penerapan Metode Full Costing Sebagai Alat Penentuan Biaya Produksi Dalam Penetapan Harga Sewa - Shita Tiara; Rukmini Rukmini (Jurnal Riset Akuntansi dan Bisnis, 2021)
This study aims to determine the full costing method which is used as a means of determining production costs in determining the rental price of PT. Bintang Hock Lie Advertising is suitable to be applied with Optimal. This type of research is a comparative descriptive study. This study uses Secondary Data, namely the Billboard Production Cost Report 2018 at PT. Bintang Hock Lie Advertising Medan Branch. Data collection techniques in this study used observation techniques, library research techniques, and documentation techniques. The results of this study indicate that PT. Bintang Hock Lie Advertising Medan Branch is still not optimal in applying the Full Costing Method. This is because the company does not calculate fixed assets as depreciation expense which is an element of Fixed Factory Overhead Costs in the Cost of Production Costs. Then there is a difference in the rental price of Rp. 4,733,000, - from the calculation of the researcher according to the theory of Rp. 318,336,100, - and from the calculation of the Company, which is Rp. 313,603,100.